Immunohistochemical Assessment of Inflammation and Regeneration in Morphine-Dependent Rat Brain - Maryam Iranpour; Sadaf Torkzadeh-Tabrizi; Zeinab Khatoon-Asadi; Reza Malekpour-Afshar (Addiction and Health, 2018)
Background: Opioids are amongst the most common abused drugs. Pathologic studies on opioid abuse are limited since the evaluation of inflammation and regeneration in brain tissue is not as simple as other tissues of the body. Thus, the present study aimed to determine the relationship between the dependence on morphine and inflammatory and regenerative processes. Methods: In this experimental study, 48 male wistar rats were divided into 6 groups. The dependent groups (3 groups) received 0.4 mg/ml morphine in drinking water for 7, 28, and 56 days. The control groups (3 groups) received sucrose solution in drinking water for the same period. The histopathological studies of the brain sample were done. The slides were stained by hematoxylin and eosin (H&E) and immunohistochemistry (IHC) staining method. The areas of brain were evaluated in terms of lymphocytic infiltration and glial scar. Findings: A significant difference was observed in the mean number of cells in the glial scar of the dependent group 3 (dependent for 56 days) among the control group (P = 0.040). Further, a significant relationship was reported between the increased duration of morphine use and the number of created scar glial cells. Furthermore, a significant increase in the number of astrocytes was observed in the affected areas. Conclusion: After long-term use, opioids can result in increased number of astrocytes and creating glial scar centers in the affected areas in response to the inflammation.